1996
DOI: 10.1192/bjp.169.5.622
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Overinvolvement in Parents of Patients with Schizophrenia or Related Psychosis: Demographic and Clinical Predictors

Abstract: Our analyses indicate that characteristics of the parent and of the parent-patient dyad seem to be the most important determinants of EOI. EOI is probably not linked to psychotic relapse, but rather to affective disturbances in the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 26 publications
5
44
1
Order By: Relevance
“…The findings are also in line with the view that emotional over-involvement can be seen as an attempt to reduce the perceived stressfulness of the caring role [21,47]. It has also been argued that this way of coping might benefit some patients in the early stages of illness when they are less able to take care of themselves [1,48]. However, emotional over-involvement seems to have a detrimental effect on the caregivers' own mental wellbeing [18], and possibly on the long-term well-being of the patients [14].…”
Section: Expressed Emotion and Distresssupporting
confidence: 78%
“…The findings are also in line with the view that emotional over-involvement can be seen as an attempt to reduce the perceived stressfulness of the caring role [21,47]. It has also been argued that this way of coping might benefit some patients in the early stages of illness when they are less able to take care of themselves [1,48]. However, emotional over-involvement seems to have a detrimental effect on the caregivers' own mental wellbeing [18], and possibly on the long-term well-being of the patients [14].…”
Section: Expressed Emotion and Distresssupporting
confidence: 78%
“…On the other hand, the substance use status of the patient, amount of face-to-face contact with the key relative, being the mother and being a single parent have been found to be related to EOI levels. Perceiving the behaviour of the patient as anxious-depressive is related with both higher C/H and EOI (Bentsen et al 1996;Kavanagh 1992). Attributions on patients' disturbed behaviours have also been found to be related to EE levels.…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, Bentsen et al (43) could not find a significant relationship between EOI and symptoms assessed by a researcher. On the other side, Breitborde et al (45) indicated that the relationship between the EOI and relapse was curvilinear and that high levels of EOI exerted a toxic effect on the course of illness whereas medium levels of EOI were protective.…”
Section: Discussionmentioning
confidence: 90%
“…Until recently, the importance of patients' perceptions of their families' attitudes were not given the necessary importance. However, although not many, there are some studies in the literature considering the importance of PEE (18,43). Thompson et al (15) found that overall patients' perceptions and caregivers' attitudes nearly overlapped.…”
Section: Discussionmentioning
confidence: 99%